PERGERAKAN PEJUANG PEREMPUAN DI KOTA MAKASSAR PASCA KEMERDEKAAN 1945-1960 - Burhanuddin, Burhanuddin; Makkelo, Ilham Daeng (Historia, 2023)
This research aims to explain the dynamics of the women's movement in Makassar City after the Indonesia Proclamation of Independence (1945-1960). During the physical revolution, women participated in the battlefield by involving themselves as nurses, taking care of public kitchens, and being active in the army. Once Indonesia received recognition of sovereignty, women began to form and develop various organizations that were active in the social, economic, educational, cultural, and political fields. In Makassar, female figures such as Emmy Saelan, Siti Mulyati Hasyim, Salawati Daud, and Milda Mathilda Towoliu were recognized. By 1955, some of them were actively involved in the Indonesian parliament. This research relies on historical research by tracing static archives, magazines, and newspapers of the time along with related literature. The research found that the experience during the physical revolution, followed by the regional upheaval in the 1950s, became the background for the women's ideas of unity and love for the motherland, involving themselves in politics in Makassar. Keywords: Equality movement; Women heroes; Makassar City